2001
DOI: 10.1289/ehp.01109383
|View full text |Cite
|
Sign up to set email alerts
|

Associations of blood pressure and hypertension with lead dose measures and polymorphisms in the vitamin D receptor and delta-aminolevulinic acid dehydratase genes.

Abstract: Evidence suggests that lead and selected genes known to modify the toxicokinetics of lead--namely, those for the vitamin D receptor (VDR) and delta-aminolevulinic acid dehydratase (ALAD)--may independently influence blood pressure and hypertension risk. We report the relations among ALAD and VDR genotypes, three lead dose measures, and blood pressure and hypertension status in 798 Korean lead workers and 135 controls without occupational exposure to lead. Lead dose was assessed by blood lead, tibia lead measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 56 publications
3
48
0
2
Order By: Relevance
“…Studies have compared associations of blood lead and bone lead with blood pressure and/ or hypertension in two populations with current or former occupational lead exposure (2,4,5) and three populations whose lead exposure was mainly from nonoccupational sources (6-9) (table 1). In the latter studies, only bone lead was associated with blood pressure or hypertension status, despite a large number of studies that have reported strong and consistent relations of blood lead and blood pressure when blood lead was the only lead biomarker measured (10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Studies have compared associations of blood lead and bone lead with blood pressure and/ or hypertension in two populations with current or former occupational lead exposure (2,4,5) and three populations whose lead exposure was mainly from nonoccupational sources (6-9) (table 1). In the latter studies, only bone lead was associated with blood pressure or hypertension status, despite a large number of studies that have reported strong and consistent relations of blood lead and blood pressure when blood lead was the only lead biomarker measured (10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…The associations of lead with systolic and diastolic blood pressure and hypertension have been previously reported in this population. 54 Many mechanisms have been proposed for how lead could increase blood pressure; it is important to evaluate gene-environment interaction, like we have here, because if eNOS genotype does not modify the relation of lead dose with blood pressure, this provides evidence that lead is unlikely to act through the eNOS gene product to influence blood pressure. Such studies thus have relevance for understanding the mechanism of lead toxicity.…”
mentioning
confidence: 72%
“…54 A polymerase chain reaction (PCR)-based assay was adapted from Hibi et al to genotype individuals for the polymorphism. 58 The primer sequences were 5Ј-TCCCTGAGGAGGGCAT-GAGGC T-3Ј and 5Ј-TGAGGGT-CACACAGGTTCCT-3Ј.…”
Section: Genotyping Assaysmentioning
confidence: 99%
“…VDR genotype was also associated with diastolic blood pressure; lead workers with the VDR B allele had diastolic blood pressures that were 1.9-2.5 mm Hg higher than in lead workers with the VDR bb genotype (p = 0.04). In addition, compared to lead workers with the VDR bb genotype, workers with the VDR B allele had a higher prevalence of hypertension (adjusted odds ratio (95% confidence interval) = 2.1 (1.0, 4.4), p = 0.05) and a larger increase in blood pressure with age (Lee et al, 2001). …”
Section: Genetic Polymorphisms and Lead Toxicitymentioning
confidence: 96%